The Effectiveness of Hydroshooter (Needle Cover Syringe) In Reducing Dental Anxiety during Local Anaesthesia - Nor Azlina Ismail ,; Nusima Mohamed ,; Nurul Amirah Yusof ,; Nurul Hanisah Binti Mohd Fauzi ,; Nasadila Nadhira Binti Nasseri (GLOBEEDU Group, 2024)
Introduction Dental fear and anxiety are frequently associated with the use of needles and syringes for local anaesthesia due to its appearance, especially in dentally anxious children. Aim & Objectives The aim of this study is to study the effectiveness of Hydroshooter cover in reducing dental anxiety towards local anaesthesia injection. The objectives of this study are to assess the dental anxiety of patient during local anaesthetic injection based on the patient’s perspective and to compare the effect of Hydroshooter cover and Conventional syringe in reducing dental anxiety during local anaesthesia injection. Methods This study involved a sample of 4 to 12 years’ old healthy patients that came for dental treatment using local anaesthetic at USIM dental polyclinic. A questionnaire with Modified Child Dental Anxiety Scale (MCDAS) was designed to collect the data from the patients. The questionnaires were filled in two different appointment; each for either local anaesthetic with Hydroshooter cover or local anaesthetic with conventional method. Result. Data was available for 38 patients with a mean of age 8 years. Overall, 70% of the patients were dentally anxious towards dental appointment and about 80% of the patients reported feeling anxious about having an injection in the gum. For the conventional syringe, 88% of the patients scored 4 and 5 for the local anaesthetic experience compared to only 15% of patients reported anxious to receive local anaesthetic with Hydroshooter cover. Conclusion The Hydroshooter cover is effective in reducing the dental anxiety amongst patient during the local anaesthesia injection. This is corresponding with the reduction of dental anxiety score for almost 50% compared to the conventional syringe.